Effect of Pesticide Use on Crop Production and Food Security in Uganda - Nakato, Linda; Kabanda, Umar; Nakitende, Pauline; Lallemant, Tess; Muyanga, Milu (Food Security Policy Research, Capacity, and Influence (PRCI), 2024)
The increasing pest proliferation has continued to cause a serious threat to food security in Uganda. This study explores the impact of pesticide adoption on food security in Uganda. Specifically, it seeks to assess whether the use of pesticides ensures food security, with crop productivity serving as an intervening variable. Employing the control function approach with fixed effects estimation on a dataset comprising 1,656 households spanning the periods 2013/2014, 2016/2015, and 2018/19 to 2019/20 obtained from the Uganda National Panel Survey, the study reveals several determinants influencing pesticide use in Uganda. The findings also highlight that the adoption of pesticides demonstrates a positive influence on crop productivity. However, when assessed through indicators such as Food Consumption Score (FCS), Minimum Acceptable Household Food Consumption (MAHFP), and Household Dietary Diversity Score (HDDS) at the pre-harvest stage, the results do not indicate a statistically significant correlation of pesticide use and food security outcomes. Consequently, beyond enhanced crop productivity and the pre-harvest activities focused on in the study, it is imperative to consider the post-harvest application of pesticides to comprehensively explain how pesticide use effects food security in Uganda. Based on the positive link between pesticides and crop productivity, its recommended that government should increase awareness on and access of insecticides among farmers. Given that insects are the main pests damaging crops in Uganda. It is also important for Uganda to reform and reactive a regulatory framework having a licensing system to regulate private local market dealers’ sale of pesticides. Given that the majority of the households purchase their pesticides from private traders in the local/village market. This approach might improve the quality of pesticide purchased by farmers and, increase pesticide use to diversify produce of more nutritious foods, to ultimately enhance access and nutrient intake per meal in Uganda.